Investigation of UPQC Performance Using PI and ANN Controller - Kumar, N. Suneel; Sri, K. Swarna (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2015)
Power Quality in electrical networks is one of the most concerned areas of preset electrical power systems. Unified Power Quality Conditioner (UPQC) is the most efficient and effective modern custom power device used in power distribution networks. A reliable control algorithm provides best performance of UPQC and at the same time the switching circuit should have fast response procedures. Artificial neural network (ANN) is considered as a new tool to design control circuitry for power quality (PQ) devices. In this paper, an ANN based controller is designed for the current control of the shunt active power filter, and is trained offline using data from the conventional proportional-integral (PI) controller.Performance of UPQC using PI controller and ANN controller are studied and compared. This performance study is carried out using MATLAB simulations.